1996
DOI: 10.1093/ageing/25.2.139
|View full text |Cite
|
Sign up to set email alerts
|

The Management of Urinary Incontinence in Residential and Nursing Homes for Older People

Abstract: We assessed the management of urinary incontinence amongst older people in residential and nursing homes and examined strategies for continence care in the homes. A random sample of local authority and private residential and nursing homes was drawn from an earlier census of long-term care. Strategies for continence care, the standard of care provided and the need for more help were determined by means of a structured questionnaire and the observations of a continence adviser. A random selection of residents i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…52 Although there are four main designs of body-worn pads available in disposable and washable variants (inserts, diapers, T-shaped diapers and pull-ups) ( Table 51), disposable products dominate and washables are more seldom used in homes. Insert pads are the simplest, cheapest (on a per product basis) and most commonly used of the disposable designs in the UK, although diaper designs are also frequently used.…”
Section: Background Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…52 Although there are four main designs of body-worn pads available in disposable and washable variants (inserts, diapers, T-shaped diapers and pull-ups) ( Table 51), disposable products dominate and washables are more seldom used in homes. Insert pads are the simplest, cheapest (on a per product basis) and most commonly used of the disposable designs in the UK, although diaper designs are also frequently used.…”
Section: Background Summarymentioning
confidence: 99%
“…There are also indications that designs vary in how long they take to apply and remove; however, this has not been demonstrated clinically. 51 Several studies have shown that incontinence is a costly aspect of care in nursing homes, 52 including laundry, disposal and staff changing costs in addition to the purchase price of the products. The choice of containment method is likely to affect significantly the overall expenditure, 53 but it is not known which designs of product are most cost-effective.…”
Section: Background Summarymentioning
confidence: 99%
“…Incontinence training programmes are documented to be effective in reducing urinary incontinence (Schnelle et al ., 1990; Yu et al ., 1990; Colling et al ., 1992; Long, 1985), but nursing home staff show low compliance with the programmes (Schnelle et al ., 1990; Campbell et al ., 1991; Cheater, 1993; Lekan‐Rutledge, 1998). Studies have shown not only that education is crucial for implementation, but also that staff communication and support is important (Schnelle et al ., 1995; Peet et al ., 1996; Lekan‐Rutledge, 1998). Urinary incontinence is under‐reported and frequently overlooked by health professionals (Cheater, 1993; Grealish, 1998): some long‐term care providers seem to passively accept urinary incontinence in older people and fail to actively intervene (Freundl & Dugan, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…For example, two separate surveys by Peet et al (1995) (n = 6079) and Roe and Shiels (2000) (n = 652) found that around a third of residents from residential homes had a continence problem. Eighty seven per cent of homes in the Peet et al (1996) survey reported using aids and appliances. Both studies claimed that in only two-thirds of the homes was promotion or management of continence adequate.…”
Section: Specific Health Needs: Identification and Managementmentioning
confidence: 99%